Fingerprint and authenticity roasted coffees by 1H-NMR: the Brazilian coffee case - Toci, Aline Theodoro; de Moura Ribeiro, Marcos Vinícius [UNESP]; de Toledo, Paulo Roberto Aparecido Bueno [UNESP]; Boralle, Nivaldo [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Springer Nature, 2018)
With globalization, it has become necessary to adopt policies to regulate the coffee market, addressing problems including the authenticity and traceability of products. It is therefore important to establish methodologies that can help to safeguard the interests of producer countries and add value to products. For this purpose, the use of NMR combined with multivariate statistical procedures can be an attractive option. The aim of this study was to develop a fast and effective technique, using 1H NMR coupled with multivariate statistics, to create a fingerprint of roasted coffees, distinguishing them according to the main Brazilian producer regions. Several compounds suitable for differentiating roasted coffees were identified in the fingerprint. Discriminant analysis revealed good distinction among the samples. The compounds catechol, trigonelline, caffeine, and n-methylpyridine were most important for the differentiation. The findings should assist coffee-producing countries in adopting measures to protect their markets and to add value to coffee products.
Keywords: Authenticity; Coffee; Discriminant analysis; Fingerprint; NMR; Traceability